A Taxonomic Revision of Photinia integrifolia (Rosaceae) - Pathak, Mitra Lal; Idrees, Muhammad; Gao, Yundong; Gao, Xin-Fen (Phytotaxa, 2019)
Taxonomic revision of a single species complex of Photinia integrifolia (Rosaceae) is accomplished during the revision of the genus Photinia sensu stricto. The study is based on the protologues and type specimens deposited in relevant herbaria. Thirty-two names are recorded for a single species. Five names are proposed as new synonyms, six lectotypes are designated, two names are identified as nomen nudum and three names are considered to be illegitimate. Taxonomic notes with type specimens, locality, and distribution for each taxon are provided.